The kidnapping of Ingrid Betancourt - Bruce, Victoria; Hayes, Karin; Home Box Office (Firm); Cinemax (Firm) (New York, NY : Women Make Movies, 2003)
"In February 2002, in the midst of her controversial campaign for president, Senator Ingrid Betancourt was kidnapped by the Revolutionary Armed Forces of Colombia (FARC) and became one of the thousands of victims of Colombia's 40-year-old civil war. Her impassioned calls for an end to political corruption and Colombia's vicious civil war had made her a popular public figure, but a dangerous instigator to many within her country's political machine. Following the candidate up to the moments before her disappearance, this remarkable film continues to tell the riveting story of her family's desperate and continuing quest to free her and keep her campaign alive"--Women Make Movies web site.
DVD.
English and Spanish with English subtitles.
Keywords: Betancourt, Ingrid, -- 1961-; Women presidential candidates -- Colombia; Colombia -- Politics and government -- 1974-; Kidnapping victims -- Colombia